2010
DOI: 10.1002/jemt.20938
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural comparison of the ocelli of Sinopanorpa tincta and Bittacus planus (Mecoptera)

Abstract: On the contrary to compound eyes, dorsal ocelli are poorly investigated for their ultrastructure in many insect groups, including Mecoptera. The ocellar ultrastructure of the scorpionfly Sinopanorpa tincta (Navás) in Panorpidae and the hangingfly Bittacus planus (Cheng) in Bittacidae was examined using transmission electron microscope. Both species possess three ocelli on the vertex of their heads and each ocellus has a corneal lens, some pigment cells at the outer rim of the lens, and fused rhabdoms. Beneath … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is astonishing considering the well-developed compound eyes and ocelli in this genus and the fact that the same study found an opsin with a long- and two opsins with a short wavelength peak absorbance in the mecopteran genus Boreus 21 . While compound eye, ocellar and larval eye ultrastructure has been investigated in some depth 22 – 27 , only two studies so far dealt with opsins in scorpionflies (Mecoptera) 21 , 28 and their closest relative order 29 , the fleas (Siphonaptera) 28 .…”
Section: Introductionmentioning
confidence: 99%
“…This is astonishing considering the well-developed compound eyes and ocelli in this genus and the fact that the same study found an opsin with a long- and two opsins with a short wavelength peak absorbance in the mecopteran genus Boreus 21 . While compound eye, ocellar and larval eye ultrastructure has been investigated in some depth 22 – 27 , only two studies so far dealt with opsins in scorpionflies (Mecoptera) 21 , 28 and their closest relative order 29 , the fleas (Siphonaptera) 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The holometabolous larva was thought to be early de‐embryonized, premature hatching, and essentially a free‐living embryo that is caused by a reduction in the amount of yolk stored in the egg (see Truman and Riddiford,1999). Under the control of juvenile hormones, the holometabolous larva was supposed to be derived from a pronymphal stage of hemimetabolous insects before hatching (Truman and Riddiford,1999).…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionary origin of holometabolous larvae is a long‐standing and controversial issue, which has not been satisfactorily resolved to date (Strathmann,1993; Sly et al,2003). Regarded as an essentially free‐living embryo caused by a reduction in the amount of yolk stored in the egg, the holometabolous larva is thought to be evolved from a hemimetabolous pronymph (see Truman and Riddiford,1999). Recently, Williamson (2009) advocates the hypothesis that caterpillar is acquired by hybridogenesis of a primitive insect with an onychophoran.…”
Section: Introductionmentioning
confidence: 99%
“…Then they were infiltrated successively through three mixtures of acetone/Epon‐812 resin (3:1 for 2 h, 1:1 for 4 h, and 1:3 for 12 h) and pure Epon‐812 resin for 24 h twice at room temperature. The samples were embedded in pure Epon‐812 resin with nadic methyl anhydride as hardener, dodecenyl succinic anhydride as softener, and 2,4,6‐tri(dimethylaminomethyl)phenol (DMP‐30) as epoxy accelerator, and finally polymerized at the temperatures of 30°C for 24 h and 60°C for 48 h (Wei and Hua, ).…”
Section: Methodsmentioning
confidence: 99%